Morphological and Molecular Characterization of Trichoderma Isolates from Vegetable Crop Rhizospheres in Nepal [version 2; peer review: 1 approved, 2 approved with reservations] - Arvind Kumar Keshari; Suraj Baidya; Aashaq Hussain Bhat; Ram B. Khadka; Puja Jaiswal (F1000Research)
Background Trichoderma spp. hold significant potential as biocontrol agents in agriculture due to their antagonistic properties against plant pathogens. The study aimed to characterize and identify Trichoderma isolates from rhizospheric regions of vegetable crops. Methods In this study, Trichoderma isolates were collected from rhizospheric soil samples of vegetable crops from different ecological zones and were selected for comprehensive morphological and molecular characterization. The isolates were visually assessed for colony color, growth pattern, aerial mycelium presence, phialide and conidial morphology, and chlamydospore presence. Molecular analysis was employed based on ITS and tef-1α sequences. Diversity indices were also computed for different ecological zones. Results The morphological characteristics and phylogenetic trees for both regions provided a clear species resolution, with four main clades: Harzianum, Viride, Brevicompactum and Longibrachiatum with 12 species T. harzinaum, T. afroharzianum, T. lentiforme, T. inhamatum, T. camerunense, T. azevedoi, T. atroviride, T. asperellum, T. asperelloides, T. koningii, T. longibrachiatum and T. brevicompactum and nine species as a new country record. Diversity indices indicated that high mountain regions displayed the highest species diversity and evenness (H = 1.724 [0.28], J = 0.84, D = 0.28), followed by hilly regions (H = 1.563 [0.28], J = 0.72, D = 0.28). Plains, on the other hand, exhibited lower species diversity (H = 1.515, J = 0.66, D = 0.33). The calculated species abundance values showed that plains (E = 2.11), mid-hills (E = 1.95), and high mountains (E = 1.99) each had their unique diversity profiles. Notably, T. afroharzianum and T. asperellum were predominant. Conclusions Overall, the study unveiled a rich diversity of Trichoderma species in different agricultural zones of Nepal. These findings shed light on the ecological distribution and diversity of Trichoderma spp., which could have significant implications for sustainable agriculture and biological control strategies.